2004
DOI: 10.1210/en.2004-0909
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Treatment of Hypothyroid Rats Restores the Regenerative Capacity and the Mitochondrial Membrane Permeability Properties of the Liver after Partial Hepatectomy

Abstract: We have investigated the effect of thyroid hormone on recovery of liver mass and on the mitochondrial membrane permeability properties during rat liver regeneration after 70% partial hepatectomy (PH). In the euthyroid state, liver weight starts to recover 24 h after PH and is completely restored 96 h after PH. Cyclosporin A (CsA)-sensitive mitochondrial permeability transition (MPT) occurs 24 h after PH, and it has been suggested to act in the signaling mechanism for hepatocyte proliferation. In this study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
5
22
0
Order By: Relevance
“…Hypothyroidism is a prevalent disorder associated with low oxygen utilization and low tissue proliferation rate (Moro et al, 2004). In the present study, PTU was observed to induce decrease in hepatocyte nuclei in Group II rats, which was evident from the decreased nuclear count.…”
Section: Discussionsupporting
confidence: 50%
“…Hypothyroidism is a prevalent disorder associated with low oxygen utilization and low tissue proliferation rate (Moro et al, 2004). In the present study, PTU was observed to induce decrease in hepatocyte nuclei in Group II rats, which was evident from the decreased nuclear count.…”
Section: Discussionsupporting
confidence: 50%
“…It has been demonstrated that a single dose of T3 enhances DNA-synthesis and regenerative capacity of the liver after PH [38,39]. Consistent with these findings, recently it has been reported that although hypothyroid rats are able to regenerate their liver mass completely, the recovery is significantly delayed; whereas T3 administration to hypothyroid rats restores the liver regenerative capacity [40].…”
Section: Discussionmentioning
confidence: 52%
“…It is also well established that thyroid hormone can increase the growth of the liver after PH because injection of T3 into mice after PH increases the rate of liver regeneration (Moro et al, 2004;Alisi et al, 2005). It does not appear that CAR directly regulates the levels of T3, although ability of CAR to regulate the levels of rT3 may be akin to regulation of T3 itself.…”
Section: Resultsmentioning
confidence: 99%